The Nexus between Corporate Governance, Green Finance, and Economic Growth in Indonesia - Shanty Ratna Damayanti; Alberta Esti Handayani; Jajuk Suprijati (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives:This study aims to examine corporate governance, specifically managerial ownership, institutional ownership, the board of directors, and the audit committee, in relation to green finance and its impact on economic growth in Indonesia. Methods: This research adopted a quantitative method, utilizing secondary data as a source of information. Secondary data is data obtained indirectly by the researcher. The secondary data in this study were obtained from the official website of the Indonesia Stock Exchange (IDX), www.idx.co.id, and the official websites of each company listed on the Indonesia Stock Exchange. The secondary data consisted of annual reports and sustainability reports published annually by each company. The secondary data collected covered the period 2021 to 2024. Finding/Results: The results of this study indicate that managerial ownership, institutional ownership, the board of directors, and the audit committee influence the implementation of green finance by public companies. Conclusion: Furthermore, optimal implementation of green finance by public companies will ultimately help boost economic growth in Indonesia.